2022
DOI: 10.3389/fpsyg.2022.983534
|View full text |Cite
|
Sign up to set email alerts
|

Enriching sociocultural perspectives on the effects of idealized body norms: Integrating shame, positive body image, and self-compassion

Abstract: Body image is an integral aspect of the psychology of the self. Idealized body images are ubiquitous in both traditional media forms (e.g., magazines, television) and social media (e.g., Facebook, Instagram). The classic sociocultural model of body image (i.e., the Tripartite Influence Model) emphasizes pathways between idealized body norms, appearance comparisons, internalization of body ideals, and body dissatisfaction and its outcomes. We summarize the model and identify some issues to be addressed in futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 168 publications
0
7
0
Order By: Relevance
“…The validity and reliability of the scale were assessed by Doğan (2010). It is a self-report scale with 16 statements developed to measure an individual’s emotional, cognitive, and behavioral concerns about his/her appearance; it uses a 5-point Likert-type scale [ 1 ] not at all appropriate and [ 5 ] completely appropriate. The 1st item of the scale is coded backward.…”
Section: Methodsmentioning
confidence: 99%
“…The validity and reliability of the scale were assessed by Doğan (2010). It is a self-report scale with 16 statements developed to measure an individual’s emotional, cognitive, and behavioral concerns about his/her appearance; it uses a 5-point Likert-type scale [ 1 ] not at all appropriate and [ 5 ] completely appropriate. The 1st item of the scale is coded backward.…”
Section: Methodsmentioning
confidence: 99%
“…Noteworthy, physical appearance and body efficiency involve not only the self-perception of the impaired persons but also the reaction of other individuals to their diversity ( 28 , 29 ). In the case of vision loss subjects, particularly young women shape this concept on externally provided verbal feedback, tactile body exploration, and perceived feelings/emotions during physical and social interaction ( 30 , 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a sociocultural context, the Tripartite Influence Model (TIM) [ 2 ] posits that body image is influenced by three main sources: family, peers, and the media. However, the original model is intended to account for body dissatisfaction, and does not feature body appreciation [ 2 , 10 ]. Recently, some studies have investigated body appreciation as a moderator between sociocultural pressures and body dissatisfaction and have found that it moderates this relationship [ 11 ].…”
Section: Introductionmentioning
confidence: 99%